2017
DOI: 10.1016/j.compstruct.2016.11.046
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fibre shape and interphase on the anisotropic viscoelastic response of fibre composites

Abstract: We perform Monte Carlo analyses of the anisotropic viscoelastic response of random RVEs representing the microstructure of UD fibre composites. Both fibres and matrix are taken as isotropic viscoelastic solids; the fibres have different shapes including circular, elliptical, Reauleaux and star-shaped; they are separated from the matrix by interphase regions of different mechanical properties and thicknesses. The analyses allow determining the sensitivity of the transversely isotropic, viscoelastic response of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(9 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Pathan et al 31 developed a numerical algorithm for the generation of the RUC of unidirectionally reinforced glass fiber composite with random distribution of fibers. Also Pathan et al 32 studied the dependence of normalized viscoelastic parameters of unidirectionally reinforced composite on fiber shapes and reinforcing structure and concluded that fiber shapes as well as fiber-matrix interface affects both stiffness and damping properties of viscoelastic materials.…”
Section: Geometry Model Of the Rucmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathan et al 31 developed a numerical algorithm for the generation of the RUC of unidirectionally reinforced glass fiber composite with random distribution of fibers. Also Pathan et al 32 studied the dependence of normalized viscoelastic parameters of unidirectionally reinforced composite on fiber shapes and reinforcing structure and concluded that fiber shapes as well as fiber-matrix interface affects both stiffness and damping properties of viscoelastic materials.…”
Section: Geometry Model Of the Rucmentioning
confidence: 99%
“…Also Pathan et al. 32 studied the dependence of normalized viscoelastic parameters of unidirectionally reinforced composite on fiber shapes and reinforcing structure and concluded that fiber shapes as well as fiber–matrix interface affects both stiffness and damping properties of viscoelastic materials.…”
Section: Models and Toolsmentioning
confidence: 99%
“…We measured the viscoelastic response of the constituents and that of the UD plates along different directions and at different temperatures and frequencies. We then construct random RVEs of the ply microstructure employing a previously developed algorithm [27,29,30] which guarantees effectively random arrangements of fibres and perform Monte Carlo analyses in the commercial FE solver ABAQUS/standard. The numerical predictions are validated by the measurements and are compared to a number of existing theoretical models, in order to rank their effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…The will to increase the damping has long been a research subject in composites materials. At the microscale, recent studies show that the shape of the inclusion and the properties of interphase also has an impact on the stiffness and damping of the homogenized cell [4]. At the mesoscale, [5] shows that the mesoscale architecture of the textile composite has a strong influence on its damping for the frequencies that were studied.…”
Section: Introductionmentioning
confidence: 92%